Educação de pessoas jovens, adultas e idosas: diálogos decoloniais - Ana Luísa Zanon Alonso (2023)
This dissertation is part of the field of research into the education of young, adult and elderly people (EJA). The aim of the research was to understand the ways in which the knowledge (of self and the world) built up by adults and the elderly throughout their lives relates to their school experiences and learning. The study was carried out in the Youth and Adult Secondary Education Project (PROEMJA), an extension project at UFMG. The methodology was based on a sequence of written and oral narrative workshops developed with a group of students in their final year of secondary school. We sought to interpret the intersections of their lived experiences in dialog with the senses and meanings that each subject attributes to school education throughout their lives. In order to establish counter-hegemonic reflections, the study was guided by a dialog with anti-colonial theories. We organized the analysis of the narratives along four axes: 1. Coloniality, race, class and gender: intersections with school; 2. Work and school; 3. The school of the past and the legacy of "not knowing"; 4. Knowledge found at school. At the same time as returning to school constitutes a space-time for regaining agency, self-esteem and strengthening self-awareness for the research subjects, when they referred to the process of schooling in adulthood or old age, they revealed places of absence in themselves, in other words, the school sometimes reiterates what they "are not", "do not know" or "cannot". We consider this to be a trait that confirms the concept of coloniality in school education, as well as broadening this concept when reflected on specifically in the field of YAE. Thus, we intend to contribute to the recognition of diverse epistemologies in this form of basic education, indicating the crossing of coloniality, as well as its potential as a meeting place for multi-epistemic knowledge. In this sense, we understand that the greatest contributions of this research are in explaining how the colonial project reverberates and produces inequalities in society and education, as well as in the decolonial interpretation of the crossings experienced by the subjects who have the right to EJA.